Penguraian limbah organik secara aerobik dengan aerasi menggunakan microbubble generator dalam kolam dengan imobilisasi bakteri - Riysan Octy Shalindry; Rochmadi Rochmadi; Wiratni Budhijanto (Jurnal Rekayasa Proses, 2015)
The abundance utilization of the water in life can lead to decrease water quality in the earth. To resolve these problems an efficient alternative waste treatment is needed. This research studied the aerobic wastewater treatment using the microbubble generator (MBG) type of porous pipe and orifice as an oxygen supply (aerator) to treat artificial waste in pond of 3m x 3m x 1m dimension. Attached culture growth using pumice as biofilm media was applied. The main focus of this research was the influence of the aeration intensity variation of MBG as the result of liquid flow rate (QL) and air flow rate (QG) combination upon the decrease of organic content measured as sCOD (soluble Chemical Oxygen Demand). The value of QG was varied at 0.0150; 0.0300; and 0.0450 m3/h while QL value was varied at 12, 14, and 16 m3/h. The data obtained were evaluated based on oxygen mass transfer performance represented by the value of kL. The value of kL was used as a reference in determining the best combination of QG and QL for reducing sCOD in aerobic wastewater treatment. From the results of the research, the best combination of QG and QL for aerobic waste treatment was at QG 0.0300 m3/h and QL 14 m3/h (at 0.0450 QG m3/h). Although the research was still exploratory, the obtained trends and numbers were very useful for optimizing the MBG performance.